2012
DOI: 10.1080/03630242.2012.674091
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Late Stage Diagnosis, Treatment, and Breast Cancer-Related Death by Race, Age, and Rural Residence Among Women in Georgia

Abstract: The objectives of this study were to examine the outcomes of late stage breast cancer diagnosis, receiving first course treatment, and breast cancer-related death by race, age, and rural/urban residence in Georgia. The authors used cross-sectional and follow-up data (1992-2007) for Atlanta and Rural Georgia cancer registries that are part of the National Cancer Institute's Surveillance, Epidemiology, and End Results Program (N = 23,500 incident breast cancer cases in non-Hispanic whites or non-Hispanic African… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 30 publications
2
80
0
Order By: Relevance
“…Similarly, using data from the NCI's Surveillance, Epidemiology and End Results (SEER) registry-based data system and focusing also on the state of Georgia, Markossian and colleagues [12] evaluated disparities among women diagnosed with late stage breast cancer. Rural residency was not found to be significantly associated with risk of death from breast cancer.…”
mentioning
confidence: 99%
“…Similarly, using data from the NCI's Surveillance, Epidemiology and End Results (SEER) registry-based data system and focusing also on the state of Georgia, Markossian and colleagues [12] evaluated disparities among women diagnosed with late stage breast cancer. Rural residency was not found to be significantly associated with risk of death from breast cancer.…”
mentioning
confidence: 99%
“…Breast cancer is the most prevalent cancer in women and it is one of the few cancers for which population screening technologies are available [171] . Most of the countries represented in this review have a national-level program for two-yearly breast cancer screening, with about half recommending screening commence at 40 or 45 years and the remainder recommending that screening start at age 50 [181].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 24 included studies, 16 reported later stage at diagnosis in rural breast cancer patients [77, 78, 136, 159, 164-167, 169, 170, 172, 173, 176, 177, 179, 180], and eight studies found no rural and urban differences [161,162,168,171,174,175,178] (see Table 15). The differences in findings…”
Section: Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations